Hypofractionated Stereotactic Body Radiation Therapy With Simultaneous Integrated Boost and Simultaneous Integrated Protection in Pancreatic Ductal Adenocarcinoma. Issue 1 (January 2021) - Simoni, N.; Micera, R.; Paiella, S.; Guariglia, S.; Zivelonghi, E.; Malleo, G.; Rossi, G.; Addari, L.; Giuliani, T.; Pollini, T.; Cavedon, C.; Salvia, R.; et al.
Abstract: Aims: To evaluate the safety and feasibility of stereotactic body radiation therapy (SBRT) with simultaneous integrated boost (SIB) and simultaneous integrated protection (SIP) in borderline resectable and locally advanced pancreatic ductal adenocarcinoma. Materials and methods: Patients receiving SBRT following induction chemotherapy from January 2017 to December 2018 were included in this observational analysis. SBRT was delivered in five consecutive daily fractions by administering 30 Gy to the planning target volume while simultaneously delivering a 50 Gy SIB to the tumour–vessel interface. SIP was created by lowering the dose to 25 Gy on the overlap area between the planning target volume and the planning organ at risk volume. The primary end point was acute and late gastrointestinal grade ≥3 toxicity. Secondary end points were freedom from local progression, overall survival and progression-free survival (PFS). Results: Fifty-nine consecutive patients (27 borderline resectable and 32 locally advanced) were included. Fifty-eight patients (98.3%) completed the SBRT planned treatment and 35 patients (59.4%) received surgical resection following SBRT. No acute or late grade ≥3 SBRT-related adverse events were observed. The median follow-up time was 15.1 months in the overall cohort and 18.1 months in censored patients. One- and 2-year freedom from local progression rates were 85% and 80% versus 79.7% and 60.6% in resected and unresected patients, respectively ( P  = 0.33). The median overall survival and PFS were 30.2 months and 19 months from diagnosis and 19.1 months and 10.7 months from SBRT in the entire cohort. Resected patients had improved 2-year overall survival rates (72.5% versus 49%, P  = 0.012) and median PFS (13 months versus 5 months; P  < 0.001) relative to unresected patients. There was no survival difference between borderline resectable and locally advanced patients. Conclusions: SBRT with SIB/SIP had an excellent toxicity profile and could be administered safely on pancreatic ductal adenocarcinoma patients, even in a total neoadjuvant setting. Highlights: The SBRT with SIB/SIP may help the safe delivery of ablative doses to the tumour. No acute or late grade ≥ 3 SBRT-related adverse events were observed with SIB/SIP. Borderline resectable pancreatic cancer patients are more likely to benefit from SBRT with SIB/SIP.